St. Anselm of Canterbury (1033-1109 AD): His Contributions to the Intellectual Developments on Medieval Scholasticism - Hendra Thamrindinata (Universitas Pelita Harapan, 2020)
Medieval scholasticism, considering its perennial influence for six centuries in the European universities, is an important intellectual power that deserves to be taken into account. In order to obtain a clearer picture of medieval scholasticism, it is necessary to have a precise understanding on the contributions of early medieval scholastic theologians who have laid the foundation for its subsequent developments. Therefore, this article will elaborate the thought of St. Anselm of Canterbury by analyzing his relevant works conceptually, discovering aspects of his thought which are foundational and significant for the subsequent intellectual developments of medieval scholasticism, exposing these aspects in detail, and tracing their influences on later theologians or periods. This elaboration finds four aspects of his thought and will expose it in detail: his view on faith seeking understanding, on teaching methodology, on the doctrine of satisfaction, and on the necessity of incarnation and satisfaction. The detailed exposition of these four aspects will substantiate the title conferred on him by Ulrich G. Leinsle as “the father of scholasticism.”